SEMANTIC ANALYSIS OF THETA ROLES OF VERBS IN THE MAH MERI LANGUAGE - Maisarah Maisarah; Kais Amir Kadhim; Zahid Ali Veesar (English Review: Journal of English Education, 2016)
The Mah Meri language, one of the severely endangered languages of Malaysia, is facing the threat of extinction. In order to save valuable information of this language, this paper focuses on one of its aspects, the Theta Roles in relation to the verbs. Using Radford’s (1997 2009) theory of Theta Roles, this study analyzes and explores the verb phrase of Mah Meri. The main objective of this study is to establish the Theta Roles in relation to verbs in the Mah Meri language. In order to fully understand the verb structures, the morphological entities of affixes such as prefixes and suffixes are studied. Moreover, the word order of the sentential constructions are also analyzed according to active and passive forms. These are done in tandem with analyzing the pronouns in relation to the placement of verbs in a Mah Meri sentential construction. It is found that Theta Roles are present in the data except for the Theta Role Recipient. However, this is not due to the lack of the Theta Role of Recipient in the Mah Meri language; rather it is due to the limitation of the scope in this study as data is analyzed based on the interviews only. On the other hand, the Theta Role of Agent is clearly evident in the Mah Meri language.Keywords: Mah Meri Language, Argument Structure, Theta Roles, Thematic Relations